A Semantic Study Of The Correlation Of Modern Embryology With Primary Arabic Literature/ دراسة دلالية لعلاقة علم الأجنة الحديث بالأدب العربي - Maqbool Ahmed; Abdul Rasheed; Amber Ghani (Ijaz Arabi Journal of Arabic Learning, 2026)
This study aims to explore the semantics of primary Arabic literature. It compares insights from modern embryology with the texts of the Quran and Hadith. Furthermore, it will attempt to extract key findings that align with modern medical knowledge and authentic religious texts. The semantics of the verse on fetal development in the mother's womb go through several distinct stages. The word "nutfah" (a drop of sperm), which is then transformed into a clot (alaqah), and then into a lump of flesh (mudghah), which takes place over a period of one hundred and twenty days. After this, the bones form and are covered with flesh, culminating in the breath of the soul into the fetus. Some researchers suggest that human development occurs over a period of eighty-four days, while others extend this period to the twenty-fourth week of pregnancy. However, most contemporary scholars interpret the stage after mudghah, when bones begin to develop and become covered with flesh, followed by the stage in which the fetus acquires the ability to survive outside the womb.